Technology and the economy - Giovanni Dosi; Luigi Orsenigo; Mauro Sylos Labini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
The paper, as such a draft of a chapter for the second edition of the 'Handbook of Economic Socielogy', Edited by Neil J. Smelser and Richard Swedberg, is meant to offer some sort of roadmap accross a few fields of investigation concerning the relationships between technological learning and economic dynamics. Within this broad critical endeavour, one discusses some of the interpretative achievements stemming from e.g. the economics of innovation, industrial economics, epistemilogy of knowledge, economic sociology and history of technology among others. In particular, one tries to identify the drivers of technological change, possible invariances in the processes of change themselves, their social and institutional roots and some properties of the dynamic coupling between technological learning, forms of corporate organization and economic evolution.
Keywords: 330; innovation; technological paradigms; trajectories; organizational capabilities; institutional embeddedness; co-evolution; Technischer Fortschritt; Lernprozess; Wirtschaftswachstum; Innovation; Theorie